1979
DOI: 10.1139/m79-007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-fat dry milk on recovery of staphylococcal thermonuclease from foods

Abstract: Modification of the method of Tatini et al. (1976) by addition of non-fat dry milk (NFDM) to food samples and subsequent acid precipitation at pH 3.8 enhanced the recovery of staphylococcal thermonuclease (TNase) from most of 37 foods tested. The modified TNase assay method allowed detection of 10 ng (0.002 units) of the enzyme per gram of each of the following foods: ground beef, boiled egg products, whey powder, fruit-containing yogurt, dressings and spreads, potato and egg salads, and pastas, all of which g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Steaming the casings before the assay caused a slight decrease in zone diameters on both assay media. The results (Table 1) demonstrated that about 2.5 to 5 ng of staphylococcal thermonuclease could be detected on the salami casing disks and that the sensitivity of this method was comparable to the levels reported previously (7,12,22). Six lots of salami with thermonuclease-positive and -negative sticks were chosen to evaluate the thermonuclease casing tests.…”
supporting
confidence: 59%
“…Steaming the casings before the assay caused a slight decrease in zone diameters on both assay media. The results (Table 1) demonstrated that about 2.5 to 5 ng of staphylococcal thermonuclease could be detected on the salami casing disks and that the sensitivity of this method was comparable to the levels reported previously (7,12,22). Six lots of salami with thermonuclease-positive and -negative sticks were chosen to evaluate the thermonuclease casing tests.…”
supporting
confidence: 59%
“…The resultant solution is then used in the thermonuclease assay. This extraction procedure has been used predominantly in the MAD assay (Niskanen and Nurmi, 1976;Park ^ a]^., 1978Park ^ a]^., , 1979Tatini et , 1976) ,…”
Section: Thermonuclease Test In Meatsmentioning
confidence: 99%